2016
DOI: 10.18632/oncotarget.10194
|View full text |Cite
|
Sign up to set email alerts
|

MT2-MMP induces proteolysis and leads to EMT in carcinomas

Abstract: Epithelial-mesenchymal transition (EMT) is critical for carcinoma invasiveness and metastasis. To investigate the role of membrane-type-2 matrix metalloproteinase (MT2-MMP) in EMT, we generated lentiviral constructs of wild-type (WT) and an inactive Glu260Ala (E260A) mutant MT2-MMP and derived stably transfected HCT116 and A549 cell lines. WT-transfected cells appeared mesenchymal-like, whereas cells transfected with the E260A mutant were epithelial-like, as were cells treated with an MMP inhibitor (GM6001). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Also, two independent studies showed that depletion of endogenous MT1-MMP or MT2-MMP reduced the basement membrane invasive activity in the MDA-MB-231 cell line (Hotary et al, 2006;Ota et al, 2009). Further, MT2-MMP is shown to degrade E-cadherin by its proteolytic activity, leading to epithelial-mesenchymal transition, and thereby facilitates cell invasion (Liu et al, 2016). Consistent with these reports, we observed that depletion of MT2-MMP led to abrogation of Matrigel invasion activity (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Also, two independent studies showed that depletion of endogenous MT1-MMP or MT2-MMP reduced the basement membrane invasive activity in the MDA-MB-231 cell line (Hotary et al, 2006;Ota et al, 2009). Further, MT2-MMP is shown to degrade E-cadherin by its proteolytic activity, leading to epithelial-mesenchymal transition, and thereby facilitates cell invasion (Liu et al, 2016). Consistent with these reports, we observed that depletion of MT2-MMP led to abrogation of Matrigel invasion activity (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…What is more, the mortality of EOC is directly related to the prevalence of metastatic diseases [21]. EMT is an important process that culminates with loss of epithelial traits and gain of mesenchymal traits [22]. In recent studies, a crucial link has been discovered between the acquisition of metastatic traits in cancer cells and the EMT.…”
Section: Discussionmentioning
confidence: 99%
“…EMT promotes the transformation of immobile epithelial cells into motile mesenchymal cells, enhancing the metastatic properties [69,70]. Further, adherens and tight junctions become impaired, resulting in a mesenchymal phenotype [12,[71][72][73]. Altered E-and N-cadherin levels and the following β-catenin activation promote the expression of many tumor-associated proteins, including cyclin D1, CD44, or c-MYC [54,[74][75][76][77][78][79].…”
Section: Introductionmentioning
confidence: 99%